Faith communities and social cohesion: The case of congregations in the Apostolic Faith Mission of South Africa - Andrew, Daniel; Schoeman, Willem J; Botes, Lucius JS (Stellenbosch Theological Journal, 2022)
After 27 years of freedom and democracy, South Africa still struggles to make the ideal of a united, democratic, free, non-racial, non-sexist society a reality. International research indicates that the lack of social cohesion is not unique to the South African context, as other countries are faced with the same challenges. Faith communities and, in particular congregations, have a role to play in addressing these challenges. The study is interdisciplinary and investigates social capital theory to see how faith communities can be repositories of social, religious, and spiritual capital that bring about social cohesion; and interrogates intergroup contact theory to see how intergroup contact theory can reduce prejudice among diverse groups in faith communities. A qualitative methodology is followed and focus group interviews are conducted in multicultural congregations of the Apostolic Faith Mission of South Africa. The study finds that faith communities can provide much needed social capital to reduce prejudice in multicultural congregations that aggregate to social cohesion in society.